CuFeS2 / poplar-based hard carbon composite material as well as preparation method and application thereof
Through the preparation of CuFeS2/popular hard carbon composite material, the self-foaming of polyvinylpyrrolidone and glucose prevent metal agglomeration were used to solve the problem of insufficient performance of hard carbon materials in sodium ion batteries, and the battery performance with high first-term efficiency, long cycle life and high reversible specific capacity was achieved.
Patent Information
- Application Number
- CN202510354215.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-03-25
AI Technical Summary
The existing sodium ion battery negative electrode material hard carbon material has low first-term efficiency, low reversible capacity, short cycle life and poor reversible specific capacity in sodium ion batteries. In addition, traditional high-temperature calcination methods lead to metal agglomeration, large particle size of the compound and uneven distribution, resulting in a decrease in sodium storage active sites and poor battery performance.
CuFeS2/popular hard carbon composite material is used to form a high closed-cell hard carbon content through self-foaming of polyvinylpyrrolidone and carbonization of poplar. The metal salt agglomeration is prevented by glucose, and CuFeS2 nanocompounds with smaller particle size and uniform distribution are prepared to form a composite material.
The first effect, cycle life and reversible specific capacity of sodium ion batteries have been significantly improved, with the first effect increased from 62.5% to 94.5%, and the reversible specific capacity has reached 510.5~548.7mAh/g. The capacity retention rate is still high after 300 cycles, which is suitable for sodium ion batteries.
Smart Images

Figure CN119858910A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of sodium ion batteries, and specifically relates to a CuFeS 2 / Poplar wood-based hard carbon composite material and its preparation method and application. Background Art
[0002] Compared with fully commercialized lithium-ion batteries, sodium-ion batteries have the advantages of abundant resources, low cost, and excellent high and low temperature performance. They are considered by researchers to be one of the ideal energy storage devices in the future. Nowadays, sodium-ion battery positive electrode materials such as layered metal oxides, Prussian blue / white materials, and polyanion compounds have been widely studied and applied, and excellent research results have been achieved. As for negative electrode materials, since the radius of sodium ions is much larger than that of lithium ions, the graphite negative electrode that can store lithium in lithium-ion batteries cannot be used in sodium-ion batteries. However, hard carbon materials have better sodium storage performance in sodium-ion batteries due to their wider lattices.
[0003] According to the source of the precursor, hard carbon materials can be divided into resin-based, biomass-based and asphalt-based derived carbon materials. Due to the wide availability of biomass, low price, self-doping elements and high residual carbon rate, biomass has been widely used by researchers in the negative electrode of sodium-ion batteries and has achieved excellent electrochemical performance. One of the typical representatives is Japan's Kuraray hard carbon material, which is derived from coconut shell carbonization and exhibits extremely high first efficiency and reversible capacity in battery applications. However, the preparation process of Kuraray hard carbon material is strict and the source of raw materials is limited, so the selling price is extremely high and there is no cost advantage. However, some other hard carbon materials derived from biomass materials such as bamboo, peanut shells, and poplar wood still face problems such as low first efficiency of charge and discharge, low reversible capacity, short cycle life and poor reversible specific capacity in sodium-ion battery applications.
[0004] In order to improve the initial efficiency of hard carbon materials in sodium-ion batteries, researchers have improved the materials by improving the reversible capacity of the low-voltage platform. Through research, it was found that some hard carbon materials with high closed-pore content are compounded with some metal sulfides, such as MoS 2 、CoS 2 、TiS 2 In the process of sodium intercalation and deintercalation, they easily form sodium metal sulfides with sodium ions and have high sodium storage reversibility. Therefore, these compounds have high first efficiency and reversible specific capacity in sodium ion battery applications. However, the material often expands greatly due to sodium intercalation and deintercalation, which makes the material pulverize and greatly reduces the battery cycle life. Compared with monometallic sulfides, bimetallic sulfides have better conductivity and higher sodium storage performance. The literature ACS Applied Materials & Interfaces 2021 13 (22), 26034-26045 first reported a chalcopyrite CuFeS negative electrode material used in sodium ion batteries. 2The authors used a conventional high-temperature method to synthesize polycrystalline CuFeS 2 Its excellent conductivity and high crystallinity enable it to exhibit excellent cycle performance in sodium-ion batteries, but the first efficiency is only 73.1%, the charge and discharge polarization is large, and the reversible specific capacity is also lacking. The main reason is that the traditional method of direct high-temperature calcination of metal salts easily causes metal agglomeration, resulting in large particle size of the compound, and the distribution of the compound in the carbon material also makes the distribution of the compound uneven, which ultimately leads to a reduction in sodium storage active sites and poor battery performance. Summary of the invention
[0005] The object of the present invention is to provide a CuFeS 2 / Poplar-based hard carbon composite material and its preparation method and application, CuFeS with smaller particle size and uniform distribution 2 Nanocompounds and poplar wood base form a hard carbon composite material with a simple preparation method and low raw material cost. It can greatly improve the initial efficiency of sodium ion batteries, and the cycle life and reversible specific capacity are improved, and can be used in sodium ion batteries.
[0006] To achieve the above object, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a CuFeS 2 / A method for preparing a poplar-based hard carbon composite material comprises the following steps: (1) washing, drying, crushing, pickling, and vacuum drying the poplar wood in sequence to obtain a pretreated material; (2) Add zinc salt and polyvinyl pyrrolidone to deionized water to prepare a mixed solution A, and add copper salt, iron salt and glucose to deionized water to prepare a mixed solution B; (3) adding the mixed solution A dropwise onto the pretreated material obtained in step (1), grinding into a viscous state, and vacuum drying to obtain a poplar-based hard carbon precursor material; (4) calcining the poplar-based hard carbon precursor material obtained in step (3) at high temperature, acid washing, and vacuum drying under an argon protective atmosphere to obtain a poplar-based hard carbon material; (5) Grind and mix the poplar-based hard carbon material obtained in step (4) with sulfur, dropwise add the mixed solution B into the mixture of the poplar-based hard carbon material and sulfur, vacuum dry, and calcine at high temperature under an argon protective atmosphere to obtain CuFeS 2 / Poplar wood-based hard carbon composite material.
[0007] Preferably, in step (2), the molar ratio of zinc salt to polyvinyl pyrrolidone is 1:1-2, the zinc salt is one of zinc nitrate, zinc chloride, zinc sulfate and zinc acetate; the molar ratio of copper salt to iron salt to glucose is 1:1:1-3; the copper salt is one of copper nitrate, copper chloride, copper sulfate and copper acetate, and the iron salt is one of iron nitrate, iron chloride, iron sulfate and iron acetate; the molar concentration of zinc salt is 0.01-0.03 mol / L, and the molar concentration of copper salt is 0.005-0.01 mol / L.
[0008] Preferably, in step (3), the vacuum drying temperature is 70-90° C. and the time is 4-8 h.
[0009] Preferably, in step (4), the high temperature calcination temperature is 1300-1500°C, the heating rate is 3-10°C / min, and the holding time is 1-3h; the pickling conditions are 2M dilute acid, stirring for 8-12h, and the vacuum drying temperature is 80-100°C for 10-24h.
[0010] Preferably, in step (5), the mass ratio of the poplar-based hard carbon material to sulfur is 1:0.05-0.1; the vacuum drying temperature is 70-90°C, the time is 4-8 hours, the high-temperature calcination temperature is 600-800°C, the heating rate is 2-5°C / min, and the holding time is 2-4 hours.
[0011] In a second aspect, the present invention provides a CuFeS prepared by the above method. 2 / Poplar wood based hard carbon composite material, the CuFeS 2 / The poplar-based hard carbon composite material comprises a matrix and nanoparticles loaded on the matrix; the matrix is poplar-based hard carbon, and the nanoparticles are CuFeS 2 Nanocompound; the poplar-based hard carbon closed-pore content is 0.68~0.83ml / g, the CuFeS 2 The particle size is 10~60nm.
[0012] In a third aspect, the present invention provides a CuFeS 2 / Application of poplar-based hard carbon composites in sodium-ion batteries.
[0013] Compared with the prior art, the present invention has the following beneficial effects: (1) CuFeS provided by the present invention 2 / Preparation method of poplar-based hard carbon composite material, in the process of pyrolysis, by using polyvinyl pyrrolidone self-foaming and poplar carbonization to form high closed-cell content hard carbon, the closed-cell capacity can reach 0.68~0.83ml / g; in the formation of CuFeS 2 In the process, glucose was used to hinder the aggregation of metal salts, making CuFeS2 Particle size reduction, CuFeS 2 The particle size is 10-60nm and is evenly distributed on the poplar-based hard carbon. The synergistic effect of the two provides more active sites for the sodium deintercalation reaction of the battery. This method is simple and easy to implement, and is conducive to the preparation of composite materials of hard carbon with high closed-cell content and small particle size and highly uniform distribution of nanometal or nanometal compound.
[0014] (2) CuFeS provided by the present invention 2 / Preparation method of poplar-based hard carbon composite material, by treating poplar to form poplar-based hard carbon with high closed-pore content, and CuFeS with small particle size and uniform distribution loaded thereon 2 Nanocompounds, forming CuFeS 2 / Poplar wood-based hard carbon composites. Poplar wood-based hard carbon with closed pores increases the low voltage platform capacity and reduces the CuFeS 2 The volume expansion caused by the sodium deintercalation reaction of nanocompounds lays the foundation for the high initial efficiency of the battery; CuFeS 2 The smaller particle size and uniform distribution of nanocompounds also increase the active sites for sodium storage, and the high reversibility of sodium insertion and extraction also increases the battery's initial efficiency from 62.5% to 94.5%. The synergistic effect of the two greatly improves the performance of sodium-ion batteries.
[0015] (3) CuFeS provided by the present invention 2 / Poplar-based hard carbon composites are used in sodium-ion batteries, and the battery has excellent electrochemical performance. At a current density of 0.2A / g, the battery's reversible specific capacity can reach 510.5~548.7mAh / g, and the first efficiency can reach 85.4~94.5%. At a high current density of 1A / g, the capacity retention rate is still 83.2~90.5% after 300 cycles. Even at an ultra-high current density of 5A / g, the battery's reversible specific capacity can still reach 280.5~320.7 mAh / g. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The CuFeS prepared in Example 1 2 / Scanning electron microscope (SEM) image of poplar-based hard carbon composite; Figure 2 The CuFeS prepared in Example 1 2 / Transmission electron microscopy (TEM) image of poplar-based hard carbon composites; Figure 3 The CuFeS prepared in Example 1 2 / X-ray diffraction (XRD) pattern of poplar-based hard carbon composites; Figure 4 The CuFeS prepared in Comparative Example 3 2 / Transmission electron microscopy (TEM) image of poplar-based hard carbon composites; Figure 5 The CuFeS prepared in Example 1 and Comparative Examples 1-3 2 / The first cycle charge and discharge curve of poplar-based hard carbon composite material; Figure 6 The CuFeS prepared in Example 1 2 / Cycling performance diagram of poplar-based hard carbon composite material at a current density of 1A / g; Figure 7 The CuFeS prepared in Example 1 2 / Reversible specific capacity diagram of poplar-based hard carbon composites at different current densities. DETAILED DESCRIPTION
[0017] The present invention is further described below by way of examples and drawings, but the protection scope of the present invention is not limited thereto. Example 1
[0018] (1) washing, drying, crushing, pickling, and vacuum drying the poplar wood in sequence to obtain a pretreated material; (2) Add 0.057 g zinc nitrate and 0.067 g polyvinyl pyrrolidone to 10 ml deionized water to prepare mixed solution A. Add 0.019 g copper nitrate, 0.024 g ferric nitrate and 0.036 g glucose to 10 ml deionized water to prepare mixed solution B. Both solutions are set aside. (3) Add the mixed solution A dropwise to 4 g of the pretreated material obtained in step (1), grind it into a viscous state, and vacuum dry it at 80 °C for 8 h to obtain a poplar-based hard carbon precursor material, then heat it to 1500 °C at 5 °C / min in an argon atmosphere and calcine it for 3 h. After cooling, stir it in 2M hydrochloric acid for 12 h, filter it, wash it with deionized water until it is neutral, and vacuum dry it at 100 °C for 24 h to obtain a poplar-based hard carbon material. (4) 0.8 g of the poplar-based hard carbon material obtained in step (3) was ground and mixed with 0.08 g of sulfur, and the mixed solution B was added dropwise to the mixture of the poplar-based hard carbon and sulfur. After vacuum drying at 80 °C for 8 h, the mixture was heated to 700 °C at a rate of 5 °C / min in an argon atmosphere and maintained for 3 h to obtain CuFeS 2 / Poplar wood-based hard carbon composite material.
[0019] The CuFeS obtained in this example 2 / Poplar wood-based hard carbon composites, loaded with CuFeS 2 The particle size of nanocompound particles is 10~25nm. Example 2
[0020] (1) washing, drying, crushing, pickling, and vacuum drying the poplar wood in sequence to obtain a pretreated material; (2) Add 0.027 g zinc chloride and 0.022 g polyvinyl pyrrolidone to 10 ml deionized water to prepare mixed solution A. Add 0.011 g copper chloride, 0.013 g ferric chloride and 0.014 g glucose to 10 ml deionized water to prepare mixed solution B. Keep both solutions aside. (3) Add the mixed solution A dropwise to 4 g of the pretreated material obtained in step (1), grind it into a viscous state, and vacuum dry it at 90 °C for 4 h to obtain a poplar-based hard carbon precursor material, then heat it to 1400 °C at 10 °C / min in an argon atmosphere and calcine it for 2 h, cool it and continue stirring it in 2 M nitric acid for 8 h, then filter it and wash it with deionized water until it is neutral, and vacuum dry it at 90 °C for 10 h to obtain a poplar-based hard carbon material; (4) 0.8 g of the poplar-based hard carbon material obtained in step (3) was ground and mixed with 0.064 g of sulfur, and the mixed solution B was added dropwise to the mixture of the poplar-based hard carbon and sulfur. After vacuum drying at 90 °C for 4 h, the mixture was heated to 800 °C at a rate of 3 °C / min in an argon atmosphere and maintained for 2 h to obtain CuFeS 2 / Poplar wood-based hard carbon composite material.
[0021] The CuFeS obtained in this example 2 / Poplar wood-based hard carbon composites, loaded with CuFeS 2 The particle size of nanocompound particles is 30~60nm. Example 3
[0022] (1) washing, drying, crushing, pickling, and vacuum drying the poplar wood in sequence to obtain a pretreated material; (2) Add 0.016 g zinc sulfate and 0.0167 g polyvinyl pyrrolidone to 10 ml deionized water to prepare mixed solution A. Add 0.008 g copper sulfate, 0.020 g iron sulfate and 0.027 g glucose to 10 ml deionized water to prepare mixed solution B. Both solutions are set aside. (3) Add the mixed solution A dropwise to 4 g of the pretreated material obtained in step (1), grind it into a viscous state, and vacuum dry it at 70 °C for 6 h to obtain a poplar-based hard carbon precursor material, then heat it to 1300 °C at 3 °C / min in an argon atmosphere and calcine it for 1 h. After cooling, stir it in 2 M sulfuric acid for 10 h, filter it, wash it with deionized water until it is neutral, and vacuum dry it at 80 °C for 12 h to obtain a poplar-based hard carbon material. (4) 0.8 g of the poplar-based hard carbon material obtained in step (3) was ground and mixed with 0.04 g of sulfur, and the mixed solution B was added dropwise to the mixture of the poplar-based hard carbon and sulfur. After vacuum drying at 70 °C for 6 h, the mixture was heated to 600 °C at a rate of 2 °C / min in an argon atmosphere and maintained for 3 h to obtain CuFeS 2 / Poplar wood-based hard carbon composite material.
[0023] The CuFeS obtained in this example 2 / Poplar wood-based hard carbon composites, loaded with CuFeS 2 The particle size of nanocompound particles is 15~40nm. Example 4
[0024] (1) washing, drying, crushing, pickling, and vacuum drying the poplar wood in sequence to obtain a pretreated material; (2) Add 0.055 g zinc acetate and 0.067 g polyvinyl pyrrolidone to 10 ml deionized water to prepare mixed solution A. Add 0.02 g copper acetate, 0.021 g ferric acetate and 0.036 g glucose to 10 ml deionized water to prepare mixed solution B. Keep both solutions aside. (3) Add the mixed solution A dropwise to 4 g of the pretreated material obtained in step (1), grind it into a viscous state, and vacuum dry it at 90 °C for 8 h to obtain a poplar-based hard carbon precursor material, then heat it to 1500 °C at 5 °C / min in an argon atmosphere and calcine it for 2 h. After cooling, stir it continuously in 2M hydrochloric acid for 12 h, filter it, wash it with deionized water until it is neutral, and vacuum dry it at 90 °C for 12 h to obtain a poplar-based hard carbon material. (4) 0.8 g of the poplar-based hard carbon material obtained in step (3) was ground and mixed with 0.08 g of sulfur, and the mixed solution B was added dropwise to the mixture of the poplar-based hard carbon and sulfur. After vacuum drying at 80 °C for 8 h, the mixture was heated to 700 °C at a rate of 5 °C / min in an argon atmosphere and maintained for 3 h to obtain CuFeS 2 / Poplar wood-based hard carbon composite material.
[0025] The CuFeS obtained in this example 2 / Poplar wood-based hard carbon composites, loaded with CuFeS 2 The particle size of nanocompound particles is 10~30nm. Comparative Example 1
[0026] The difference from Example 1 is that polyvinyl pyrrolidone is not added to the mixed solution A in step (2), and the other steps remain unchanged. Comparative Example 2
[0027] The difference from Example 1 is that no glucose is added to the mixed solution B in step (2), and the other steps remain unchanged. Comparative Example 3
[0028] The difference from Example 1 is that in step (2), no polyvinyl pyrrolidone is added to the mixed solution A, and no glucose is added to the mixed solution B. The other steps remain unchanged. Comparative Example 4
[0029] The electrode materials obtained in Examples 1-4 and Comparative Examples 1-3 were mixed with Super P conductive carbon black and polyvinylidene fluoride in a mass ratio of 8:1:1 in N-methylpyrrolidone to form a slurry with suitable viscosity, which was then coated on an aluminum foil, dried, compacted and cut into suitable sizes to obtain a negative electrode sheet for a sodium ion battery, which was then assembled with a Whatman GF / A glass fiber membrane, an electrolyte containing 1.5 M sodium hexafluorophosphate in ethylene carbonate-diethyl carbonate-ethyl methyl carbonate (volume ratio of 1:2:2), and a metal sodium sheet into a button cell for electrochemical performance testing. The test results are shown in Table 1.
[0030]
[0031] As can be seen from the above table, Examples 1-4 have higher closed cell capacity. Combined with the TEM image of Example 1 ( Figure 2 ), CuFeS 2 The nanocompound particles are evenly distributed and have a small particle size. The higher closed-pore capacity not only increases the low-voltage platform capacity of the battery, but also alleviates the CuFeS 2 The volume expansion caused by the sodium insertion and extraction, in addition, CuFeS 2 The inherent characteristics of the nanocompound particles also increase the sodium storage active sites. At a current density of 0.2A / g, the battery reversible specific capacity can reach 510.5~548.7mAh / g, and the first efficiency can reach 85.4~94.5%. At a high current density of 1A / g, there is still a capacity retention rate of 83.2~90.5% after 300 cycles. Even at an ultra-high current density of 5A / g, the battery reversible specific capacity can still reach 280.5~320.7 mAh / g. Therefore, Examples 1-4 show a higher first efficiency, a higher cycle retention rate and an excellent reversible specific capacity.
[0032] Figure 1 The CuFeS prepared in Example 1 2 / SEM image of poplar wood-based hard carbon composite material, Figure 2 is the corresponding TEM image, Figure 3 It can be seen from the SEM and TEM images that CuFeS 2 / Poplar wood-based hard carbon composite material is a blocky irregular material, consisting of a hard carbon matrix and a 10-25nm uniformly loaded CuFeS 2 Nanocompound particle composition, CuFeS 2The smaller particle size and uniform distribution of nanocompounds can increase the active sites for sodium storage, and the high reversibility of sodium insertion and extraction can also improve the initial efficiency of the battery. 2 The main diffraction peaks (112), (220), (204) and other crystal planes are consistent with the standard PDF card numbers, and the diffraction peak around 22.6° is the poplar-based hard carbon peak.
[0033] Figure 5 This is the charge and discharge curve of the first cycle of Example 1. Figure 6 is the cycle performance diagram of Example 1 at a current density of 1 A / g, Figure 7 The reversible specific capacity diagram of Example 1 at different current densities. Example 1 shows a high initial efficiency of 94.5%. After activation at a lower current density of 0.2A / g, it still has a capacity retention rate of 90.5% after 300 cycles at a high current density of 1A / g. Compared with Examples 1-4, Comparative Example 1 lacks closed-cell capacity, so the low-voltage platform capacity is reduced. Although Comparative Example 2 also has a higher content of closed-cell capacity than Examples 1-4, it does not have the hindering effect of glucose pyrolysis carbon, and CuFeS 2 The particles will be dispersed disorderly, and the particle size will be larger due to the agglomeration of the metal. Compared with Examples 1-4, Comparative Example 3 contains less closed pore capacity, CuFeS 2 The disorder and particle size further increase ( Figure 4 ). In summary, Comparative Example 3 exhibits the worst electrochemical performance due to the lack of closed-pore capacity and uniform, small-sized CuFeS 2 During the first discharge cycle, too much sodium salt is consumed to obtain a higher irreversible capacity, and there is almost no low-voltage platform capacity, resulting in too low charging capacity, that is, the first efficiency is extremely low, only 62.5%, and there is almost no capacity at high current densities of 2A / g and 5A / g.
[0034] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. Ordinary technicians in the field should understand that the present invention can still be modified or replaced by equivalents to achieve the same technical effects; as long as the use requirements are met, they are within the protection scope of the present invention.
Claims
1. A method for preparing a CuFeS2 / poplar-based hard carbon composite material, characterized in that: The steps include: (1) washing, drying, crushing, pickling, and vacuum drying the poplar wood in sequence to obtain a pretreated material; (2) Add zinc salt and polyvinyl pyrrolidone to deionized water to prepare a mixed solution A, and add copper salt, iron salt and glucose to deionized water to prepare a mixed solution B; (3) adding the mixed solution A dropwise onto the pretreated material obtained in step (1), grinding into a viscous state, and vacuum drying to obtain a poplar-based hard carbon precursor material; (4) calcining the poplar-based hard carbon precursor material obtained in step (3) at high temperature, acid washing, and vacuum drying under an argon protective atmosphere to obtain a poplar-based hard carbon material; (5) Grind and mix the poplar-based hard carbon material obtained in step (4) with sulfur, dropwise add the mixed solution B into the mixture of the poplar-based hard carbon material and sulfur, vacuum dry, and calcine at high temperature under an argon protective atmosphere to obtain a CuFeS2 / poplar-based hard carbon composite material.
2. The method for preparing the CuFeS2 / poplar-based hard carbon composite material according to claim 1, characterized in that: In the step (2), the molar ratio of the zinc salt to the polyvinyl pyrrolidone is 1:1-2, and the zinc salt is one of zinc nitrate, zinc chloride, zinc sulfate and zinc acetate; the molar ratio of the copper salt to the iron salt to the glucose is 1:1:1-3; the copper salt is one of copper nitrate, copper chloride, copper sulfate and copper acetate, and the iron salt is one of iron nitrate, iron chloride, iron sulfate and iron acetate; the molar concentration of the zinc salt is 0.01-0.03 mol / L, and the molar concentration of the copper salt is 0.005-0.01 mol / L.
3. The method for preparing the CuFeS2 / poplar-based hard carbon composite material according to claim 1, characterized in that: In the step (3), the vacuum drying temperature is 70-90° C. and the time is 4-8 hours.
4. The method for preparing the CuFeS2 / poplar-based hard carbon composite material according to claim 1, characterized in that: In the step (4), the high temperature calcination temperature is 1300-1500°C, the heating rate is 3-10°C / min, and the holding time is 1-3h; the pickling conditions are 2M dilute acid, stirring for 8-12h, and the vacuum drying temperature is 80-100°C for 10-24h.
5. The method for preparing the CuFeS2 / poplar-based hard carbon composite material according to claim 1, characterized in that: In the step (5), the mass ratio of the poplar-based hard carbon material to sulfur is 1:0.05-0.1; the vacuum drying temperature is 70-90°C, the time is 4-8 hours, the high-temperature calcination temperature is 600-800°C, the heating rate is 2-5°C / min, and the holding time is 2-4 hours.
6. A CuFeS2 / poplar-based hard carbon composite material obtained by the preparation method according to any one of claims 1 to 5, characterized in that: The CuFeS2 / poplar-based hard carbon composite material includes a matrix and nanoparticles loaded on the matrix; the matrix is poplar-based hard carbon, and the nanoparticles are CuFeS2 nanocompounds; the poplar-based hard carbon closed-pore content is 0.68-0.83 ml / g, and the CuFeS2 particle size is 10-60 nm.
7. An application of the CuFeS2 / poplar-based hard carbon composite material as claimed in claim 6, characterized in that: The CuFeS2 / poplar-based hard carbon composite material is applied to sodium ion batteries.
Citation Information
Patent Citations
Method for preparing metallic oxide-carbon composite material
CN105006575A
Wood-based composite hard carbon negative electrode material and preparation method and application thereof
CN115304052A
Porous silicon-carbon composite material, preparation method thereof and application of porous silicon-carbon composite material in secondary battery
CN117766742A
Preparation method and application of hard carbon negative electrode material based on poplar
CN118439591A
Devices comprising a carbonaceous material, and uses of the material
WO2017160237A1